Answer is ( 2, 5 )
Step by step
To solve this system of equations, substitute the value of y from equation 1 in for y in equation 2. They will equal each other.
4x -3 = -2x + 9
Add 2x to both sides to combine variables
4x + 2x -3 = -2x + 2x + 9
Simplify
6x -3 = 9
Add 3 to both sides to combine constants
6x -3 +3 = 9 + 3
Simplify
6x = 12
Divide both sides by 6 to solve for x
6/6 x = 12/6
x = 2
Now sub the value of x = 2 into the first equation and solve for y
y = 4 (2) -3
y = 8 -3
y = 5
Your solution is ( 2, 5)
Or you can enter the two equations into a graphing calculator and find where the two lines cross, that is also your solution. See attachment